Unmistakable morphology?: infantile malignant osteopetrosis resembling juvenile myelomonocytic leukemia in infants - Strauss, Anne; Buchholz, Bernd (The journal of pediatrics, 2015)
The initial clinical and hematologic presentation of infantile malignant osteopetrosis may be indistinguishable from that of juvenile myelomonocytic leukemia in infants. Timely radiographic imaging, however, allows straightforward delineation of these 2 severe diseases and facilitates immediate initiation of appropriate therapy.